Sorting the Muck from the Brass: Analysis of Protein Complexes and Cell Lysates - Zoltner, Martin; Del Pino, Ricardo Canavate; Field, Mark C (Methods in molecular biology (Clifton, N.J.), 2020)
Reliable determination of protein complex composition or changes to protein levels in whole cells is challenging. Despite the multitude of methods now available for labeling, analysis, and the statistical processing of data, this large variety is of itself an issue: Which approach is most appropriate, where do you set cutoffs, and what is the most cost-effective strategy? One size does not fit all for such work, but some guidelines can help in terms of reducing cost, improving data quality, and ultimately advancing investigations. Here we describe two protocols and algorithms for facile sample preparation for mass spectrometric analysis, robust data processing, and considerations of how to interpret large proteomic datasets in a productive and robust manner.
Keywords: multiproteinové komplexy; Sample preparation; datové soubory jako téma; elektroforéza v polyakrylamidovém gelu; SDS-PAGE; Electrophoresis, Polyacrylamide Gel; Proteomics; Multiprotein Complexes; MaxQuant; Mass Spectrometry; proteomika; Data presentation; Trypanosoma; Protozoan Proteins; Datasets as Topic; protozoální proteiny; Trypanosoma brucei brucei; hmotnostní spektrometrie